Effect of Intraperitoneal Application of 1% Methylene Blue Solution on Prevention and/or Reduction of Adhesion Following Laparotomy in Rabbits: Bahjat Taifor Abbas1 and Sozan Ali Mohammed - Abbas, Bahjat Taifor (The Iraqi Journal of Veterinary Medicine, 2012)
The effect of 1% methylene blue solution was investigated in this experimental trial for prevention and/or reduction of intra-abdominal adhesion formation, following induction of conventional laparotomy, by postmortem and histopathological confirmations, in a rabbit model. Twenty adult, male, local breed rabbits were used in the study. They were allocated randomly and equally into 2 groups; Control group (CG) and Treatment group (TG). All were subjected to mid-ventral conventional laparotomy under the effect of general anesthesia, and the ascending colon was exteriorized and its serosal and subserosal layers were mechanically abraded by a dry sterile soft toothbrush. In TG, 2ml of sterile 1% methylene blue was applied intrapretonially prior to the routine closure of the abdominal cavities. While in CG, 2ml of physiological saline solution was applied intraperitonially. Post-operatively, the rabbits were monitored clinically for; gain in body weight, food intake and postoperative complications. Also, 5 rabbits from each group at the 14th and 21st post-operative days were scarified for intra-peritoneal adhesion formation and scoring, and biopsy collection for histopathological changes. The results revealed a significant reduction and/or prevention in the development of intra-abdominal adhesions in TG compared to CG rabbits. Whereby, the lowered adhesions grade scores rate at both P.M. schedules, and histopathologically by the normally appearing serosal and muscular layers of the caecum, compared to the abnormally higher losses in the integrity of the serosal surface, blood vessel congestion, fibrosis, and heavy infiltrated of mononuclear inflammatory cells in CG rabbits. This study concluded that, the application of 1% methylene blue solution intraperitoneally following laparotomy is useful in preventionand/or reduction of post-operative adhesions formation.